Dinamika Pembelajaran Hifzu Mutun: Identifikasi Kendala, Respons Siswa, dan Strategi Solutif di Lingkungan Pesantren - Muhammad Fadhil; Mulhendra; Hari Febriansyah (STIT Hidayatunnajah Bekasi, 2023)
This study aims to identify key obstacles to digital transformation in elementary madrasas, particularly in video-based thematic learning. It examines the impact of infrastructure, digital skills, and psychological factors on implementation, alongside adaptive responses within the teacher agency framework. Using a qualitative-phenomenological design, data were gathered through in-depth interviews, observations, and document analysis. Thematic analysis was employed to map relationships between barriers and emerging strategies.Findings reveal multidimensional obstacles, including connectivity issues, device limitations, and challenges in curating video content aligned with Islamic values. However, teachers demonstrate strong agency through adaptive strategies like offline video use, language localization, and peer tutoring. The study concludes that digital barriers are surmountable through creativity and collaboration. Recommendations include sustainable infrastructure improvements, curated video repositories, and practical technical training to support the Merdeka Curriculum.